Thermal Calculation of Oil-Gas Burner for Two-Stage Burning of Gaseous Fuel - G. I. Zhikhar; I. G. Zhikhar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals the procedure of thermal calculation of oil-gas burner for two-stage burning of natural gas.